2011
DOI: 10.1016/j.jmb.2011.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Function of Tim50 in the Mitochondrial Presequence Translocase

Abstract: Many mitochondrial proteins are synthesized as preproteins carrying amino-terminal presequences in the cytosol. The preproteins are imported by the translocase of the outer mitochondrial membrane (TOM) and the presequence translocase of the inner membrane (TIM). Tim50 and Tim23 transfer preproteins through the intermembrane space to the inner membrane. We report the crystal structure of the intermembrane space domain of yeast Tim50 to 1.83 Å resolution. A protruding β-hairpin of Tim50 is crucial for interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(93 citation statements)
references
References 30 publications
8
84
1
Order By: Relevance
“…Chemical shift changes upon addition of pSu9N were enhanced at higher KCl concentrations for the C-terminal segment of sPBD while those for the N-terminal segment of sPBD were not affected or even suppressed at higher KCl concentrations. Therefore the C-terminal segment, but not the N-terminal part of sPBD, interacts with pSu9N through hydrophobic interactions, which is consistent with the recent suggestion that the interactions between Tim50 and presequences are mainly hydrophobic rather than hydrophilic [8,9,11,17].…”
Section: Interaction Between Spbd and A Presequence Is Partly Hydrophsupporting
confidence: 90%
See 1 more Smart Citation
“…Chemical shift changes upon addition of pSu9N were enhanced at higher KCl concentrations for the C-terminal segment of sPBD while those for the N-terminal segment of sPBD were not affected or even suppressed at higher KCl concentrations. Therefore the C-terminal segment, but not the N-terminal part of sPBD, interacts with pSu9N through hydrophobic interactions, which is consistent with the recent suggestion that the interactions between Tim50 and presequences are mainly hydrophobic rather than hydrophilic [8,9,11,17].…”
Section: Interaction Between Spbd and A Presequence Is Partly Hydrophsupporting
confidence: 90%
“…Tim50IMS contains a well-conserved domain (residues 159-362) followed by the C-terminal tail that is conserved only among fungal species (residues 363-476). A trypsin resistant core domain (IMS-core: residues 164-361) in the conserved IMS domain was subjected to crystallization, and its X-ray structure was reported [8]. The determined X-ray structure of residues 176-361 consists of five a-helices and nine b-strands, and a negatively charged groove near the protruding b-hairpin was proposed to bind to a positively charged presequence [8].…”
Section: Introductionmentioning
confidence: 99%
“…5): the channel-forming Tim23 protein (Meinecke et al 2006;van der Laan et al 2007;Alder et al 2008); Tim17, which is involved in gating of the Tim23 channel and membrane insertion of preproteins Meier et al 2005) and Tim50, which induces the closing of the Tim23 protein-conducting channel in the absence of preproteins (Meinecke et al 2006). Tim50 exposes a large domain to the IMS, which is in close proximity to the outer membrane TOM complex, and together with the amino-terminal IMS domain of Tim23 constitutes the receptor domain of the TIM23 machinery Mokranjac et al 2009;Tamura et al 2009a;Marom et al 2011;Qian et al 2011;Shiota et al 2011). Two recent studies have indicated that Tim50 might have two distinct binding sites for preproteins in the conserved core domain and in the carboxy-terminal domain, respectively (Qian et al 2011;Schulz et al 2011).…”
Section: Inner Membrane Insertion and Matrix Translocation By The Timmentioning
confidence: 99%
“…2). The first subunit of the TIM23 complex encountered by an incoming precursor protein on the trans-side of the TOM complex is Tim50 (26)(27)(28)(29). Tim50 passes the presequence to the channel forming unit of TIM23 formed by the Tim23 and Tim17 proteins.…”
Section: Figmentioning
confidence: 99%